2005
DOI: 10.1562/2005-04-06-ra-477
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Visible Light Phototoxicity on Porphyromonas gingivalis and Fusobacterium nucleatum

Abstract: Phototoxicity of visible light laser on the porphyrin-producing bacteria, Porphyromonas gingivalis, in the absence of photosensitizers and under aerobic conditions was shown in previous studies. Recently, we found that the noncoherent visible light sources at wavelengths of 400-500 nm, commonly used in restorative dentistry, induced a phototoxic effect on P. gingivalis, as well as on Fusobacterium nucleatum, and to a lesser extent on the Streptococci sp. To elucidate the mechanism of this phototoxic effect, P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 30 publications
2
74
0
4
Order By: Relevance
“…Under oxidative-stress conditions, KatG of B. pseudomallei plays important roles in cell survival (22). The phototoxic effect of visible light on bacteria is oxygen dependent (7). For example, exposing Porphyromonas gingivalis and Fusobacterium nucleatum to blue light under anaerobic conditions eliminates the phototoxic effect seen under aerobic conditions (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under oxidative-stress conditions, KatG of B. pseudomallei plays important roles in cell survival (22). The phototoxic effect of visible light on bacteria is oxygen dependent (7). For example, exposing Porphyromonas gingivalis and Fusobacterium nucleatum to blue light under anaerobic conditions eliminates the phototoxic effect seen under aerobic conditions (7).…”
Section: Discussionmentioning
confidence: 99%
“…The phototoxic effect of visible light on bacteria is oxygen dependent (7). For example, exposing Porphyromonas gingivalis and Fusobacterium nucleatum to blue light under anaerobic conditions eliminates the phototoxic effect seen under aerobic conditions (7). The katG mutation in B. glumae did not affect survival at the stationary growth phase but was lethal when the strain was exposed to visible light.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that exposure to visible light, more specifically, blue-light wavelengths, causes inactivation of certain bacterial species, including Propionobacterium acnes, Helicobacter pylori, and some oral pigmented bacteria (1,8,22). This inactivation mechanism, known to be oxygen dependent (6), is thought to be a result of the photoexcitation of naturally occurring endogenous porphyrins, which act as endogenous photosensitizers within the bacterial cells. This porphyrin excitation leads to energy transfer and, ultimately, the production of highly cytotoxic, oxygenderived species, most notably, singlet oxygen (11,26).…”
mentioning
confidence: 99%
“…However, a dose-dependent synergistic antibacterial effect on bacteria embedded in biofilm was demonstrated when noncoherent blue light and H 2 O 2 were applied simultaneously. It was previously shown that the phototoxic effect of noncoherent blue light on planktonic bacteria involves the formation of ROS and that hydroxyl radicals (OH ⅐ ) play an important role in this process (4,5). It is assumed that the synergistic effect on bacterial vitality in biofilm is the result not of direct fission of H 2 O 2 by light, as described for the mechanism of action of UV light, but of the generation of the highly reactive OH ⅐ radical when H 2 O 2 encounters "free Fe(II)," via the Fenton reaction (5).…”
Section: Vol 52 2008 Effects Of Visible Light and H 2 O 2 On S Mutmentioning
confidence: 99%
“…Recently, a synergistic antibacterial effect of noncoherent blue light, often used in restorative dentistry, and hydrogen peroxide (H 2 O 2 ) on S. mutans under planktonic conditions was observed (5). Due to the widespread use of antibiotics and the emergence of more resistant and virulent strains of microorganisms, there is an urgent need to develop alternative sterilization technologies that affect biofilms.…”
mentioning
confidence: 99%